EFFICIENCY OF TREATMENT OF DRUG RESISTANT PULMONARY TUBERCULOSIS IN BASHKORTOSTAN - L. Ya. Borodina; M. M. Yunusbaeva; P. M. Аlekseev; R. А. Davydov; L. А. Nikitina; S. N. Kovalevich; Kh. K. Аminev; R. А. Sharipov (Туберкулез и болезни лёгких)
.